Sandwich-like nitrogen-enriched porous carbon/graphene composites as electrodes for aqueous symmetric supercapacitors with high energy density. (20th January 2016) - Xie, Qinxing; Zhou, Shuwen; Zheng, Anran; Xie, Chao; Yin, Cuiyu; Wu, Shihua; Zhang, Yufeng; Zhao, Peng
Graphical abstract: Highlights: Novel sandwich-like porous carbon/graphene composites were prepared. A high specific capacitance of 381.6 F g −1 was achieved in 6 M KOH electrolyte. The distinct effects of two types of graphene on structure and performance were investigated. The supercapacitors deliver both high-energy density and high-power density. Abstract: Sandwich-like nitrogen-enriched porous carbon/graphene composites were prepared by carbonization of polyacrylonitrile (PAN) nanofiber paper with bulk-doped and/or surface-coated graphene oxide (GO), and followed by activation with KOH at high temperatures. The composites exhibit high specific surface areas in a range of 1957.2–2631.8 m 2 g −1, as well as superior energy storage capability as electrodes for supercapacitors. A very high specific capacitance of 381.6 F g −1 at a current density of 0.1 A g −1 was achieved in 6 M KOH aqueous electrolyte for N-ACGrF@Gr1 that contains two types of graphene. According to the investigation results, the surface-coated graphene plays a more positive effect on improved supercapacitance than the bulk-doped graphene in the composites. Additionally, the assembled aqueous symmetric supercapacitors deliver a high energy density of 13.2 W h kg −1 at a power density of 25.0 W kg −1, and 8.3 W h kg −1 at 4.7 kW kg −1 with a retention rate of 62.9%.